Divergent brain connectivity patterns in relation to cognition in Alzheimer's disease and frontotemporal dementia. (31st December 2021) - Pini, Lorenzo; de Lange, Siemon; Pizzini, Francesca B; Galazzo, Ilaria Boscolo; Manenti, Rosa; van den Heuvel, Martijn; Pievani, Michela
Abstract: Background: Divergent functional connectivity (FC) abnormalities between networks linked with core cognitive deficits have been reported in Alzheimer's disease (AD) and behavioural variant frontotemporal dementia (bvFTD), the default mode (DMN) and ventral‐attention (VAN), respectively. As cognition relies on the balance between brain networks, we investigated the coupling patterns between different cognitive domains and networks. Method: Twenty‐one bvFTD (age: 71±10), 22 AD (age: 72±6) and 20 healthy controls (HC, age: 72±6) underwent cognitive evaluation and 3T resting‐state functional MRI (rsfMRI). We investigated the relationship between memory, language, executive, visuospatial and emotion recognition with FC of cognitive networks: DMN, VAN, frontoparietal (FPN), and dorsal‐attention (DAN). The visual network (VIS) was included as a control network. FC was assessed with a connectome analysis. Cortical parcels were defined using a high‐resolution structural MRI parcellation. Connectivity matrices were created assessing correlations between parcels within each functional network (Yeo 2011 parcellation). Correlation values were thresholded to retain positive values. FC and cognitive differences between groups were assessed with Kruskal‐Wallis test, Spearman's correlation was used to assess relationships between FC and cognition. Result: Compared to HC, AD and bvFTD showed impairment in all cognitive domains (p<0.001), and bvFTD scored worse than AD in emotion recognition (p=0.013). At the network level, AD showed reduced FC in the DMN, FPN and DAN (p<0.05) and bvFTD in the VAN (p<0.05) compared to HC. In bvFTD, reduced VAN connectivity was associated with executive deficits (r=0.444; p=0.038). In AD, reduced FPN connectivity was associated with language deficits (r=0.441; p=0.04), while the opposite pattern was observed in bvFTD (r=‐0.468; p=0.028). Moreover, in AD patients DMN connectivity was negatively associated with executive deficits (r=‐0.56; p=0.007). A significant interaction was detected between AD and bvFTD for the following cognitive‐network associations: VAN‐executive: p=0.027; FPN‐language: p=0.015. No significant association was detected between DMN‐memory in AD or VAN‐emotion recognition in bvFTD (p>0.06), nor between cognition and VIS (p>0.09 for all associations). Conclusion: These results suggest a divergent FC‐cognitive pattern between AD and bvFTD in attention/executive networks/functions. We speculate that, as pathology spreads, disease‐specific symptom‐network coupling might weaken, and aberrant patterns may emerge in other domains.